Composición florística y estructural en una parcela permanente de bosque seco en la parroquia Mangahurco, Zapotillo-Loja - Aponte Córdova, Carmen María (2015)
Seasonally dry forests in the south-west of Ecuador are the largest and best preserved in Ecuador, but their dynamics are poorly understood, it is why these studies are conducted with the purpose of generating information to enable rational management of forest resources , The research was conducted in order to determine the floristic composition, structure and endemism in the dry forest of the "Tabanco"- Mangahurco, Zapotillo County, Loja Province. A permanent plot of one hectare (10 000 m2), divided into 25 plots of 20 x 20 m (400 m2) for individuals greater than or equal to 5 cm in diameter at breast height (DBH), nine plots of 5 x 5 m (25 m2) for shrubs and nine plots of 1 x 1 m (1 m2) for the herbaceous plants. All trees greater than or equal to 5 cm marked DAP (standardized to 1.30 m) and diameter (tape) and height (Hypsometer Sunnto) was measured; branched trees under 1.30 m tall, they were measured all stems greater than or equal to 5 cm DAP and basal area of the individual is calculated as the sum of the areas of the measured basal stems. Besides its exact position within the quadrant it was recorded by drawing a map. Ecological parameters as calculated: density, relative density, dominance, relative dominance, frequency and importance value index; based on the formulas proposed by Cerón (1993), Aguirre and Aguirre (1999). For the structure of the forest was calculated to basal area and volume by diameter class and species. Structural shapes for a transect of 10 x 100 m, where the location of the trees in the X and Y coordinates, height, distance and shape of the tree´s crown was marked.The analysis of the condition of the forest was performed by the average of epiphytes and the rubric proposed by CINFA et al., (2006); endemism recorded by comparison with the Red Book of Endemic Plants of Ecuador (León et al. 2011) and literature of Peru was revised to share endemism, Were registered 61 species, of which 32 correspond to tree layer distributed in 32 genera and 18 families, 7 shrubs , 18 herbs and 4 epiphytes were recorded. The most diverse families are Mimosaceae, Caesalpiniaceae. Fabaceae, bignoniaceae, moraceae, bomabacaceae, Rubiaceae and Verbenaceae The dry forest of the "Tabanco" of the Mangahurco parish , Canton Zapotillo , Loja Province , presented a basal area of 16.99 m2 / ha and a volume of 61,11m3 / ha. The most ecologically important species include Handroanthus chrysanthus, Simira ecuadorensis and Citharexylum gentryi From the results it can conclude the dry forest "Tabanco" is in good state of preservation. Peru - Ecuador 2 endemic species and 9 species endemic to the region shared between Ecuador Tumbesina identified.